Early-onset versus late-onset Crohn's disease: An Italian cohort study. Issue 1 (February 2020) - Cantoro, Laura; Lenti, Marco Vincenzo; Monterubbianesi, Rita; Cicala, Michele; Giannarelli, Diana; Papi, Claudio; Kohn, Anna; Sabatino, Antonio Di
Background: Disease heterogeneity, according to the age at onset, has been reported in Crohn's disease (CD). Objective: This study aimed to compare natural history in CD patients diagnosed ≤17 (early onset (EO)) versus ≥60 (late onset (LO)) years old. Methods: EO CD and LO CD patients referred to two Italian inflammatory bowel disease (IBD) centres were included. Relevant data comprised sex, current smoking, disease location and behaviour, IBD family history, extra-intestinal manifestations and use of medical/surgical therapy during the follow-up period. Results: Among 2321 CD patients, 160 met the inclusion criteria: 92 in the EO and 68 in the LO group (mean follow-up 11.7 ± 7.7 years). Family history of IBD was more frequent in EO compared to LO CD (26% vs. 4%; p < 0.0001). Ileocolonic, upper gastrointestinal and perianal involvement occurred more frequently in EO compared to LO CD (56% vs. 21%, p < 0.0001; 17% vs. 3%, p < 0.01; and 38% vs. 19%, p < 0.01, respectively). Progression to complicated disease occurred more frequently in EO CD (40% vs. 10% p < 0.005), with an increased use of corticosteroids and anti-tumour necrosis factor alpha agents within 10 years since diagnosis (81% vs. 58%, p = 0.004, and 36% vs. 16%, p = 0.01, respectively), while the cumulative probability of surgery did not differ between the two groups. Conclusions: Patients with EO CD are more likely to develop a more aggressive disease with perianal involvement and a greater use of drug treatment compared to those with LO CD, without carrying an increased need for surgery.